Técnicas quirúrgicas e ingeniería tisular con células madre de cartílago humano en reconstrucción de oreja: revisión de literatura (2023)
Microtia is the absence of the pinna of the external ear that can occur unilaterally or bilaterally, sometimes it can manifest with hearing loss, it is caused by a malformation in the formation of the ear due to traumatic situations that can affect the muscles and the structures around the ear depending on the stomatognathic system; It generally has a surgical approach, but today it is also possible to work with cartilage formation from stem cells for reconstruction, which is still under investigation and study. This review aims to cover all these techniques to evaluate the possibilities from the dental point of view and the management of maxillofacial reconstruction; since Dentistry has intervention in this aspect, not only in medicine but also in the vision of the affectation; also, in the vision of commitment to development. It is expected to determine the different surgical techniques for ear reconstruction and the implementation of tissue engineering with human cartilage stem cells; to determine the best approach for the patient. Pubmed, academic Google, Scielo databases are reviewed, which in the search are articles in the languages of English, Spanish and Portuguese in a range of years from 2017 and 2022 with the keywords Microtia, congenital, reconstructive, surgical procedure, tissue cells, treatment. It is expected that this work will be a guide for dentists and professionals who work with Microtia and ear reconstruction by orienting surgical management alternatives for patients with this alteration and the understanding of the relationship between the effects of alteration that Microtia has with the craniomaxillary development and therefore of the stomatognathic system. Keywords: Microtia, congenital, reconstructive, surgical procedure, tissue cells, treatment